2001
DOI: 10.1159/000046107
|View full text |Cite
|
Sign up to set email alerts
|

The Hematocrit-Corrected Erythrocyte Sedimentation Rate Can Be Useful in Diagnosing Inflammation in Hemodialysis Patients

Abstract: Background/Aims: We aimed to determine predictors of erythrocyte sedimentation rate (ESR), and the ESR level pointing to the presence of inflammation in 60 chronic hemodialysis (HD) patients. Methods/Results: On bivariate analysis, increased Westergren ESR of 62 (4–160) mm/h correlated inversely with hematocrit (Hct) and serum albumin, and positively with age, plasma fibrinogen, serum C-reactive protein (CRP), immunoglobulins A and G, α1-acid-glycoprotein and α1-antitrypsin. On multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 7 publications
0
21
1
Order By: Relevance
“…The most accepted inflammatory measurements used in clinical medicine are the erythrocyte sedimentation rate (ESR) and levels of C-polysaccharide reactive protein (C-reactive protein; CRP) [34]. ESR indirectly reflects potentially increasing serum proteins, such as fibrinogen, acute-phase proteins and immunoglobulins [35]. CRP is the most studied acute-phase protein and is a good measure of activity of disease because high circulating levels are correlated with the acute inflammatory stages of the disease, and low levels with quiescent stages [36].…”
Section: Introductionmentioning
confidence: 99%
“…The most accepted inflammatory measurements used in clinical medicine are the erythrocyte sedimentation rate (ESR) and levels of C-polysaccharide reactive protein (C-reactive protein; CRP) [34]. ESR indirectly reflects potentially increasing serum proteins, such as fibrinogen, acute-phase proteins and immunoglobulins [35]. CRP is the most studied acute-phase protein and is a good measure of activity of disease because high circulating levels are correlated with the acute inflammatory stages of the disease, and low levels with quiescent stages [36].…”
Section: Introductionmentioning
confidence: 99%
“…However, corrected ESR levels according to hematocrit was reported to better serve to select the inflammationafflicted HD patients. [14] In this study, these markers, selected as the indices of inflammation, and MIS were not found to be different between HCV-infected and non-infected HD patients. Nascimento et al has also investigated the effect of hepatitis C on two markers of systemic inflammationm, and they also could not find any difference between IL-6 and CRP levels of anti-HCV-positive and -negative HD patients.…”
Section: Discussionmentioning
confidence: 55%
“…Hematocritcorrected ESR was calculated using the formula ESR × (Hct ÷ 45) after measuring ESR. [14] Blood urea nitrogen, creatinine, calcium, phosphorus ALT, AST, total iron binding capacity, and lipid profile were measured with routine laboratory techniques using an automated analyzer (RocheHitachi 912, Roche Hitachi Modular Analytics, Roche Mid-arm muscle circumference = Mid-arm circumference (3. − 1 1416 triceps skinfold thickness).…”
Section: Laboratory Assessmentmentioning
confidence: 99%
“…Increased ESR in HD patients may be associated with acute-phase response, anemia, and aging. 9 Image study was indicated for all patients in ESRD with neurologic deficit, severe focal back pain, or unexplained fever with raised ESR.…”
Section: Discussionmentioning
confidence: 99%